2011
DOI: 10.1063/1.3560457
|View full text |Cite
|
Sign up to set email alerts
|

Large amplitude magnetization dynamics and the suppression of edge modes in a single nanomagnet

Abstract: Directional-dependent coercivities and magnetization reversal mechanisms in fourfold ferromagnetic systems of varying sizes J. Appl. Phys. 113, 013901 (2013) Magnetoresistance and shot noise in graphene-based nanostructure with effective exchange field J. Appl. Phys. 112, 123719 (2012) Thermally assisted spin-transfer torque magnetization reversal in uniaxial nanomagnets Appl. Phys. Lett. 101, 262401 (2012) Combined fitting of alternative and direct susceptibility curves of assembled nanostructures J.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The spectrum reveals a main peak at 4.4 GHz that is in excellent agreement with spectra extracted from micromagnetic simulations (bold line). In Keatley et al [83], the mode at 200 Oe was identified to be an edge mode. At larger bias field values, where the centre and edge modes coexist, the response of the edge mode was found to be strongly dependent on the amplitude of the pulsed field excitation.…”
Section: Magnetization Dynamics In Individual Nanomagnetsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectrum reveals a main peak at 4.4 GHz that is in excellent agreement with spectra extracted from micromagnetic simulations (bold line). In Keatley et al [83], the mode at 200 Oe was identified to be an edge mode. At larger bias field values, where the centre and edge modes coexist, the response of the edge mode was found to be strongly dependent on the amplitude of the pulsed field excitation.…”
Section: Magnetization Dynamics In Individual Nanomagnetsmentioning
confidence: 99%
“…The FFT spectrum (figure 4b) reveals a broader line width and a lower frequency. In Keatley et al [83], the shift to lower frequency and the enhanced damping were respectively ascribed to the different internal field and different magnon-magnon scattering efficiency that result from the different magnetic ground state of the square when the field was applied along the diagonal.…”
Section: Magnetization Dynamics In Individual Nanomagnetsmentioning
confidence: 99%
See 1 more Smart Citation
“…From previous studies of similar devices, the magnetization and uniaxial anisotropy field were assumed to be 860 emu cm −3 and 5 Oe for the FL, and 1800 emu cm −3 and 167 Oe for the RL, respectively [22]. For both layers the values of α, the g factor, and P were assumed to be 0.03 [13], 2, and 0.45 [23], respectively, while η was varied to achieve the best agreement with the experiment. The value of η for the RL was found to have negligible effect upon the FL dynamics and was fixed at 0.1 [10].…”
Section: Macrospin Simulationsmentioning
confidence: 99%
“…To date, the majority of experimental studies have used MR measurements in three-or four-terminal devices to study these dynamic processes [7][8][9][10]. Because of its high spatial (ß300 nm) and temporal (ß10 ps) resolution, time-resolved scanning Kerr microscopy [12] (TRSKM) has proven to be a powerful magneto-optical tool for contactless detection of magnetization dynamics in individual nanomagnets [13,14]. Here we use TRSKM to characterize the strength of the NL-STT acting on a NiFe free layer (FL) nanomagnet of a two-terminal current perpendicular-to-plane (CPP) spin valve [15,16].…”
Section: Introductionmentioning
confidence: 99%